2014
DOI: 10.1097/iae.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Pharmacology of Topotecan and Its Activity in Retinoblastoma

Abstract: Topotecan alone or in combination is active against retinoblastoma. It shows a favorable passage to the vitreous when given intravenously and intraarterially, and ocular toxicity is minimal by all routes of administration. However, its clinical role, optimal dose, and route of administration for the treatment of retinoblastoma are to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 58 publications
(76 reference statements)
0
24
0
1
Order By: Relevance
“…Seven patients out of eight received intrathecal thiotepa and one patient received thiotepa during neoadjuvant chemotherapy and topotecan during adjuvant chemotherapy because of a failure to collect peripheral stem cells. Indeed, Schaiquevich et al showed that topotecan, alone or in combination, is active against retinoblastoma and Potter et al showed that intrathecal route of administration is tolerable and active against recurrent or refractory leptomeningeal leukemia. It was therefore used in this patient because we could not intensify treatment with high‐dose chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Seven patients out of eight received intrathecal thiotepa and one patient received thiotepa during neoadjuvant chemotherapy and topotecan during adjuvant chemotherapy because of a failure to collect peripheral stem cells. Indeed, Schaiquevich et al showed that topotecan, alone or in combination, is active against retinoblastoma and Potter et al showed that intrathecal route of administration is tolerable and active against recurrent or refractory leptomeningeal leukemia. It was therefore used in this patient because we could not intensify treatment with high‐dose chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as previously published, we highlight the activity and safety of intrathecal topotecan for high‐risk retinoblastoma with CSF involvement included in this multimodality treatment . We selected intrathecal topotecan based on its activity in retinoblastoma and previous reports for intrathecal use …”
Section: Discussionmentioning
confidence: 94%
“…6). These findings may help to explain why CPT and another TOP1 inhibitor, topotecan, were found to have potent and fast activity against retinoblastoma, which is caused by the loss of RB function (Chantada et al, 2009;Han and Wei, 2011;Schaiquevich et al, 2014). In the Arabidopsis root, further work is needed to reveal the molecular basis of the genetic interaction, for instance, by analyzing the physical interaction between TOP1a and RBR.…”
Section: Discussionmentioning
confidence: 99%